Pendidikan kesehatan tentang melitus pada keluarga - rahayu, dian (Teewan Journal Solutions, 2024)
Diabtes Melitus (DM) is a disease characterized by blood glucose levels exceeding normal which is characterized by fasting and postprandial hyperglycemia, atherosclerosis and microangiopathic vascular disease. DM can be caused due to diet or genetic factors. Research conducted in Pahandut Palangka Raya Village showed a lack of family knowledge (67%) regarding DM can be a predisposing factor for the occurrence of DM in family members. Education is an effort to make people behave or adopt health behaviors by means of persuasion, persuasion, appeal, invitation, giving information, giving awareness and so on, through activities called education or health promotion. The method of implementing the activity is to use a health education strategy for families in Pahandut Palangka Raya. The activities carried out are by carrying out health education to families in Pahandut Palangka Raya. The activity is carried out with the lecture and question and answer method. The health education media used are LCD projectors and leaflets distributed to families. The material provided is about DM disease which includes understanding, causes, signs and symptoms, treatment, complications. During health education, the environment is conducive, the family enthusiastically listens to health education and actively asks when given opportunities for discussion. The results of the evaluation of health education show the family is able to mention and explain again about DM disease as described during health education. Community service activities carried out by lecturers, nurses and Ners professional students to families in Pahandut Palangka Raya can be declared successful. Through the evaluation results during health education, there is a positive response from the family and is also able to mention again about DM as described.